Stimulator of IFN genes mediates neuroinflammatory injury by suppressing AMPK signal in experimental subarachnoid hemorrhage - Peng, Yucong (J Neuroinflammation, 2020)
BACKGROUND: Neuroinflammation is closely associated with the poor prognosis in subarachnoid hemorrhage (SAH) patients. This study was aimed to determine the role of stimulator of IFN genes (STING), an essential regulator to innate immunity, in the context of SAH. METHODS: A total of 344 male C57BL/6 J mice were subjected to endovascular perforation to develop a model of SAH. Selective STING antagonist C-176 and STING agonist CMA were administered at 30 min or 1 h post-modeling separately. To investigate the underlying mechanism, the AMPK inhibitor compound C was administered intracerebroventricularly at 30 min before surgery. Post-SAH assessments included SAH grade, neurological test, brain water content, western blotting, RT-PCR, and immunofluorescence. Oxygenated hemoglobin was introduced into BV2 cells to establish a SAH model in vitro. RESULTS: STING was mainly distributed in microglia, and microglial STING expression was significantly increased after SAH. Administration of C-176 substantially attenuated SAH-induced brain edema and neuronal injury. More importantly, C-176 significantly alleviated both short-term and persistent neurological dysfunction after SAH. Meanwhile, STING agonist CMA remarkably exacerbated neuronal injury and deteriorated neurological impairments. Mechanically, STING activation aggravated neuroinflammation via promoting microglial activation and polarizing into M1 phenotype, evidenced by microglial morphological changes, as well as the increased level of microglial M1 markers including IL-1β, iNOS, IL-6, TNF-α, MCP-1, and NLRP3 inflammasome, while C-176 conferred a robust anti-inflammatory effect. However, all the mentioned beneficial effects of C-176 including alleviated neuroinflammation, attenuated neuronal injury and the improved neurological function were reversed by AMPK inhibitor compound C. Meanwhile, the critical role of AMPK signal in C-176 mediated anti-inflammatory effect was also confirmed in vitro. CONCLUSION: Microglial STING yielded neuroinflammation after SAH, while pharmacologic inhibition of STING could attenuate SAH-induced inflammatory injury at least partly by activating AMPK signal. These data supported the notion that STING might be a potential therapeutic target for SAH.